2010
DOI: 10.1186/1475-2859-9-30
|View full text |Cite
|
Sign up to set email alerts
|

A novel prokaryotic vector for identification and selection of recombinants: Direct use of the vector for expression studies in E. coli

Abstract: BackgroundThe selection of bacterial recombinants that harbour a desired insert, has been a key factor in molecular cloning and a series of screening procedures need to be performed for selection of clones carrying the genes of interest. The conventional cloning techniques are reported to have problems such as screening high number of colonies, generation of false positives, setting up of control ligation mix with vector alone etc.ResultsWe describe the development of a novel dual cloning/expression vector, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…This work demonstrates that higher the solubility of the target protein , the intensity of the GFP fluorescence on the agar plate is higher rendering the screening of the recombinants a dual objective of identification and also predicting the solubility of the gene of interest attached to the reporter gene. The article as described by Banerjee et al, (2010) demonstrates this clearly. While GCSF, a human granulocyte colony stimulating factor gene which is known to get expressed as insoluble aggregates in E. coli shows lesser fluorescence as GFP fusion (Figure 3, panel B) the E. coli methionine amino peptidase, the well soluble E. coli protein exhibits higher intensity of GFP fusion (Figure 3, panel A).…”
Section: Prediction Of Solubility Of Recombinant Clones During Screeningmentioning
confidence: 78%
See 1 more Smart Citation
“…This work demonstrates that higher the solubility of the target protein , the intensity of the GFP fluorescence on the agar plate is higher rendering the screening of the recombinants a dual objective of identification and also predicting the solubility of the gene of interest attached to the reporter gene. The article as described by Banerjee et al, (2010) demonstrates this clearly. While GCSF, a human granulocyte colony stimulating factor gene which is known to get expressed as insoluble aggregates in E. coli shows lesser fluorescence as GFP fusion (Figure 3, panel B) the E. coli methionine amino peptidase, the well soluble E. coli protein exhibits higher intensity of GFP fusion (Figure 3, panel A).…”
Section: Prediction Of Solubility Of Recombinant Clones During Screeningmentioning
confidence: 78%
“…It has been observed that CAT fusions to insoluble proteins confer lower chloramphenicol resistance than that of a fusion with highly soluble partner. Similarly, Banerjee et al, (2010) have shown that the solubility of the target protein could be predicted in situ at the time of recombinant screening based on the intensity of the GFP fusion proteins. This work demonstrates that higher the solubility of the target protein , the intensity of the GFP fluorescence on the agar plate is higher rendering the screening of the recombinants a dual objective of identification and also predicting the solubility of the gene of interest attached to the reporter gene.…”
Section: Prediction Of Solubility Of Recombinant Clones During Screeningmentioning
confidence: 99%
“…An alternative (split-GFP) system for protein interaction screening is discussed below (Jackrel et al 2010). Banerjee et al (2010) used GFP as a high-throughput cloning aid for RP production. They constructed an expression plasmid comprising a T7-inducible promoter and gfp, separated by a multiple cloning site and a TAA stop codon.…”
Section: Gfp As a Reporter In High-throughput Screeningmentioning
confidence: 99%
“…This has previously been achieved using loss-of-function vectors, in which the addition of an insert disrupts a conditionally toxic gene (e.g., the Escherichia coli ccdB gene, which encodes a lethal DNA gyrase poison) (Bernard et al 1994). However, due to selective pressure on the cell ccdB mutants can arise, giving false positives; while the requirement for cloning within an existing gene limits the ability to express the inserted gene product (Banerjee et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the fundamental aspects of other published gain-of-function positive selection vectors also limit their scope of usability. These include reliance on a specific host strain for selection of clones (Banerjee et al 2010), on noncanonical type II or other specific restriction enzymes for DNA insertion (Ohashi-Kunihiro et al 2007;Miura et al 2011), or on complete inhibition of expression of the inserted gene of interest in a manner that precludes use in expression library formation and enzyme activity screening (Malo and Husain 2003).…”
Section: Introductionmentioning
confidence: 99%